2001
DOI: 10.1002/cncr.10201
|View full text |Cite
|
Sign up to set email alerts
|

Liposome‐encapsulated doxorubicin compared with conventional doxorubicin in a randomized multicenter trial as first‐line therapy of metastatic breast carcinoma

Abstract: BACKGROUND The objective of this study was to compare the efficacy and toxicity of the liposome‐encapsulated doxorubicin, TLC D‐99 (Myocet, Elan Pharmaceuticals, Princeton, NJ), and conventional doxorubicin in first‐line treatment of metastatic breast carcinoma (MBC). METHODS Two hundred twenty‐four patients with MBC and no prior therapy for metastatic disease were randomized to receive either TLC D‐99 (75 mg/m2) or doxorubicin (75 mg/m2) every 3 weeks, in the absence of disease progression or unacceptable tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
251
2
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(272 citation statements)
references
References 24 publications
9
251
2
8
Order By: Relevance
“…In normal tissue, the intact liposomes are confined to the intravascular space, as normal blood vessels are not fenestrated to the same degree as in tumour tissue. Hence, the toxicity to normal tissue is reduced considerably, especially cardiotoxicity (Harris et al, 2002). Although liposomal delivery of doxorubicin improves the tumour uptake compared to free doxorubicin, the drug distribution within the tumour tissue is still heterogeneous (Vaage et al, 1997;Davies et al, 2004).…”
mentioning
confidence: 99%
“…In normal tissue, the intact liposomes are confined to the intravascular space, as normal blood vessels are not fenestrated to the same degree as in tumour tissue. Hence, the toxicity to normal tissue is reduced considerably, especially cardiotoxicity (Harris et al, 2002). Although liposomal delivery of doxorubicin improves the tumour uptake compared to free doxorubicin, the drug distribution within the tumour tissue is still heterogeneous (Vaage et al, 1997;Davies et al, 2004).…”
mentioning
confidence: 99%
“…14 The benefits associated with liposomal anthracyclines in breast tumors have been mainly associated with reduced cardio-toxicity rather than with a significant improvement in the outcome of patients. 15 Clinical studies using VCR encapsulated in distearoylphospatidylcholine/cholesterol (DSPC/Chol) demonstrated that liposomal VCR can be administered at higher doses than free drug and it is effective in relapsed non-Hodgkin's lymphomas (NHL). 16,17 A modification of DSPC/Chol liposomes has been introduced generating the sphingomyelin/cholesterol (SM/Chol) liposomes.…”
mentioning
confidence: 99%
“…Irreversible damage to the myocytes by free radicals, so called Type I myocardial damage, is presumed to be the cause of anthracycline-induced cardiomyopathy [22,23]. The development of encapsulated conventional anthracyclines, such as PLD have led to a reduction of the incidence and severity of cumulative dose-related cardiomyopathy while preserving antitumor activity [24][25][26][27]. Thus, PLD may offer patients the benefit of receiving higher cumulative doses (compared with conventional doxorubicin) over a longer period of time, ultimately resulting in greater drug exposure.…”
Section: Discussionmentioning
confidence: 99%